The Use of Geomembrane Technology: A Solution to Increase Hygienic Salt Production - Saisa, Saisa; Sartika, Zulhaini; Erdiwansyah, Erdiwansyah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Demand for salt in Indonesia continues to increase, while local production has not kept up and therefore relies on imports. Salt production faces challenges such as weather dependency and the risk of soil mixtures that degrade product quality. This community empowerment program aims to improve the quality and quantity of hygienic salt production in business groups through the application of geomembrane technology, and increase production capacity to meet standards. The program methods include socialization, technical training on geomembrane installation, assistance in production, and evaluation. The results and impacts of the salt production process increased by 20%, salt products produced are whiter, hygienic, and meet SNI standards. In addition, the income of the business group increased by 50%. This production has successfully improved productin efficiency and the welfare of salt farmers. In the future, the group plans to expand the market, improve infrastructure, and submit products for formal certification. Geomemran technology has proven to be an effective and sustainable solution in supporting hygienic salt production.